GAMBARAN KOMPOSISI FILUM FIRMICUTES DAN BACTEROIDETES PADA OBESITAS (STUDI LITERATUR) (Jurnal Kesehatan Siliwangi, 2022)
Obesity is a global health problem.  Recently, the composition of the gut microbiota, especially Firmicutes and Bacteroidetes, has been suggested to be one of the factors that play a role in the incidence of obesity.  The purpose of this study was to describe the composition of Firmicutes and Bacteroidetes in obesity.  The research design used is a literature study.  The literature used is journals that meet the inclusion criteria, namely a total of 6 articles.  The results of the literature study showed that there were different results on the composition of the gut microbiota in obesity.  Several journals showed that the composition of Firmicutes increased and Bacteroidetes decreased in obesity, while other studies showed Firmicutes and Bacteroidetes increased in the obese group compared to the normal weight group.  Furthermore, in another study, it was found that Bacteroidetes and Firmicutes were higher in the lean group compared to the obese group.  However, it was also found that there was no clear difference between the phyla Firmicutes and Bacteroidetes according to BMI